PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) TERHADAP KEMAMPUAN PEMAHAMAN KONSEP DAN AKTIVITAS BELAJAR PESERTA DIDIK SMPN 15 PADANG - Azyzah Gita Maulana (Jurnal Edukasi dan Penelitian Matematika, 2019)
Understanding of mathematics concept is the basic ability that must be possessed by students. But in reality, students’ understanding of mathematics concepts in grade VIII SMPN 15 Padang were still weak and learning process was still centered on educators. The solution that could be applied was the cooperative learning model type Student Teams Achievement Division (STAD) which made students active in the learning process. The purpose of the study was to find out how the learning activities of students who learned with STAD learning model and to describe students’ understanding of mathematics concepts who learned in experiment class were better than the control class. The type of research was a quasy experiment with static group design. The research hypothesis was proven by t test. From the data analysis, for the level of  , it can be concluded that the activities of students who learn with the STAD learning model fluctuated at each meeting, and students’ understanding of mathematics concepts who learn with STAD learning model is better than conventional learning models.Keywords --- conventional learning, mathematical concept, STAD learning model, student activities